Special Issue on Algorithms and Data-Structures for Compressed Computation - Policriti, Alberto; Prezza, Nicola (Algorithms, 2022)
As the production of massive data has outpaced Moore’s law in many scientific areas, the very notion of algorithms is transforming [...]